A systematic review on malaria and Tuberculosis (TB) vaccine challenges in sub-Saharan African clinical trials - Maonezi Abas Hamisi; Nur Ain Mohd Asri; Aini Syahida Mat Yassim; Rapeah Suppian (PLoS ONE, 2025)
Objective For more than a century, developing novel and effective vaccines against malaria and Tuberculosis (TB) infections has been a challenge. This review sought to investigate the reasons for the slow progress of malaria and TB vaccine candidates in sub-Saharan African clinical trials. Methods The systematic review protocol was registered on PROSPERO on July 26, 2023 (CRD42023445166). The research articles related to the immunogenicity, efficacy, or safety of malaria or TB vaccines that were published between January 1, 2012, and August 31, 2023, were searched on three databases: Web of Science (WoS), PubMed, and ClinicalTrials.gov. Results A total of 2342 articles were obtained, 50 of which met the inclusion criteria. 28 (56%) articles reported on malaria vaccine attributes, while 22 (44%) articles reported on TB vaccines. In both cases, the major challenges in sub-Saharan African clinical trials were immunogenicity and efficacy, rather than safety. Conclusion Factors such as population characteristics, pathogen genetic diversity, vaccine nature, strategy, and formulation were associated with slow progress of the malaria and TB vaccine candidates in sub-Saharan African clinical trials.